Openness in services trade and economic growth - El Khoury, Antoine; Savvides, Andreas (My University, 2006)
We examine the relationship between openness in services trade (both telecommunication and financial) and economic growth via the threshold regression model to test for a differential impact between low- and high-income countries. Results confirm the existence of a two-regime split. © 2006 Elsevier B.V. All rights reserved.
Keywords: Economic growth; Financial services; Services trade; Telecommunication services